Quand les épigrammes dialoguées se mettent à enseigner : Callimaque de Cyrène (AP VII, 524 = 31GP) et Posidippe de Pella (APl 275 = 19GP) - Hamidou Richer (Cahiers des Études Anciennes)
When dialogues with teaching purposes are studied, no one will think sua sponte of the little poems which are called ‘epigrams’. Nevertheless, this study tries to suggest how complex dialogues have gradually appeared in some of these small poems, which aimed at a sort of teaching. Focusing on epigrams which contain more than a single exchange of words, two epigrams are studied: in the first one, by Callimachus, the deceased teaches the living epigrammatist that there is nothing after death, whereas in the second one, Posidippus teaches us about the purposes of the allegory of Καιρός carved by Lysippus.